EFFICIENCY OF NITROGEN FERTILIZER APPLICATION ON WHITE CABBAGE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Nitrogen is considered to be harvest-limiting element. Almost all investigations showed that under optimal nitrogen fertilizer harvest increases despite different and contrastive environmental conditions. There is a lack of research about changes of plant photosynthetic action under nitrogen fertilizer influence. During field and laboratory experiments changes of head cabbage (‘Ancoma F1’ variety) photosynthesis - related parameters under different nitrogen supply (50, 120, 190, 190 + 40 and 190 + 50 + 40 N kg ha-1) were observed. Results of field and laboratory experiments showed that optimal nitrogen fertilizer doses are 190 and 190 + 40 N kg ha-1. The conlusion is that chlorophyll content (in SPAD readings and mg.dm-2) and fluorescence parameters (Fv/Fm, Fv/Fo, RC/ABS and PI) can be used as early indicator for forseeing nitrogen fertilizer efficiency for head cabbage. Fluorescence parameters give precise view of nitrogen fertilizer role in plant physiological processes and nitrogen effect on plant growth and development.